Hubungan Pre Eklampsia Pada Ibu Hamil dengan Kejadian BBLR di RSUD Kelas D Pondokgede - Netri Makassar; Elfira Sri Futriani (Universitas Malahayati Lampung, 2024)
ABSTRACT According to the World Health Organization (WHO) the infant mortality rate (AKB) in the world is still quite high, which is 37 per 1000 live births. One of the causes of high infant mortality (AKB) in the world is low birth weight (BBLR). The factors that cause BBLR are maternal factors, fetal factors, placental factors, and environmental factors, one of the mother's factors is Pre Eclampsia. This research aims to find out